The implementation of environmental education policy in Namibia: perceptions of a range of decision-makers - Katoma, Loini-Nyanyukweni (Rhodes University, Faculty of Education, Department of Education, 2002)
This study is the first cycle of an action research project that focuses on the implementation of the Environmental Education Policy in Namibia. Perceptions of Namibian decision-makers were sought with regard to their understanding of the concepts 'environment' and 'environmental education', as well as to identify environmental problems and obstacles to the implementation of the Environmental Education Policy. The approach of coming up with options to address the identified problems/obstacles/constraints, was employed in this study. To this effect, interviews, a workshop, observations and reflections on the process of implementation resulted in a wealth of data. The findings shed light on possible solutions to address the identified problems and obstacles. The results revealed that community participation, skills development and the proper co-ordination of environmental education activities are imperative in addressing the obvious policy-practice gap. Decision-makers uncovered the fact that the socio-economic situation of our people necessitated pulling our resources together and working as a team. The overall perceptions are that the environment is everyone's business and that we should zealously use it and carefully guard it, not only for ourselves but also, for the benefit of coming generations.
Keywords: Environmental education -- Namibia; Education and state -- Namibia